TI_GERICHTE 11.2013.26 vom 15. Juli 2015 , Iscrizione di ipoteca legale dell'artigiano o imprenditore: tempestività - TI Tribunale d'appello (2015)
Iscrizione di ipoteca legale dell'artigiano o imprenditore: tempestività